Saberes experienciais nas/com as culturas digitais no curso de Pedagogia - Carvalho, Tainah dos Santos (2023)
Faced with a society immersed in digital cultures, it is important for education professionals to reflect on and understand the presence of digital devices, applications and interfaces in education, which is why it is essential for initial teacher training courses to promote experiences involving digital technologies in order to stimulate the construction of knowledge. The aim of this research was to understand the experiential knowledge built and mobilized by Pedagogy students at the Federal University of Sergipe in training processes in/with digital cultures. It is a qualitative study, as it deals with the subjectivities and singularities of the social actors/actresses, from the perspective of a different kind of rigor for educational research. It is based on the epistemological field of multi-referentiality (ARDOINO, 1998) and the type of research used is critical ethno-research (MACEDO, 2010). The research site was the Prof. Alberto Carvalho Campus of the Federal University of Sergipe, located in Itabaiana, Sergipe. The social actors/actresses of the research were nine students on the Pedagogy degree course. The devices used to produce the data were conversation circles, held in person and online, and a memory wall, produced using the Padlet application. The research findings were systematized and interpreted using cognitive operations (MACEDO, 2010; 2021). In this process of interpretation, the following subsuming notions emerged: (Trans)formations: digital technologies in the Pedagogy course and Digital cultures and the construction of experiential knowledge in initial training, the latter of which is broken down into two sub-notions, namely: Ethnomethods with digital technologies in the training process and Construction of being a teacher with digital cultures. Based on the analysis of the data, it was found that the social actors/actresses in the research have been immersed in digital cultures even before they started their undergraduate studies and course activities, and that non-presential teaching, which took place during the COVID-19 pandemic, broadened these students' contact with various technologies, promoting experiences that enhanced and (trans)formed the learning-teaching process. Therefore, contact with digital technologies culminated in the construction of experiential knowledge, collective and collaborative production, the development of ethnomethods and reflection on and in teaching practice.